Koncepcja zarządzania wiedzą w projektach informatycznych - Wojtkiewicz-Wydra, Ewa (Knowledge Management Conception in IT-projects, 2006)
Within the framework of the following study it has been proposed to depict knowledge management in the light of (and in relation to) IT-projects. In the first part of the paper main trends in the development of knowledge management has been shown. It has been based on K.E. Sveiby's conception, which joins two approaches to the problem: IT and individual. Moreover a combination of characteristics of IT-projects has been presented. These characteristics mould a peculiarity and procedures of knowledge management process (in their field). In the last part identification of elements which form the process in IT-projects has been carried out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 199-208